Clinical outcomes of nonvariceal upper gastrointestinal bleeding in Kosova - Telaku, Skender; Kraja, Bledar; Qirjako, Gentiana; Prifti, Skerdi; Fejza, Hajrullah (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim was to determine the sociodemographic and etiologic factors, endoscopic accuracy, treatment efficiency and clinical outcome of patients with nonvariceal upper gastrointestinal system bleeding in Kosova. Materials and Methods: We retrospectively evaluated patients who had applied to our Gastroenterology Department between January 2006 and December 2010. Results: There were 460 eligible cases with mean age 56.85+16.18 years, while male /female ratio was 2.71/1. The greatest occurrence was at age group of 60-69 years (27.1 %). The most common clinical symptom was melena (62.6%). Comorbid diseases were present in 57, 6% of the patients. The percentage of patients using acetylsalicylic acid and /or other non-steroidal anti-inflammatory drugs was 43.7%. Five point two percent were using anticoagulants. Peptic ulcer was the main cause of bleeding (82.2%) and most of them were Forrest III (41.6%). Endoscopic treatment was performed in 90 patients, primary hemostasis was achieved in 96.7% while rebleeding developed in 10% of these patients. The average length of hospital stay was 9.29+5.58 (1-35) days. Rebleeding was reported in 4.1% of all patients while the overall mortality rate was 5.7%. Conclusion: Age over 60 years, previous history of gastrointestinal bleeding, treatment with anticoagulants, low hemoglobin values at presentation(< 7g/dL), hematemesis, Forrest class, localization of lesion of bleeding, comorbidities, tachycardia, transfusion requirement > 2 unit, type of treatment and time of endoscopy were predictors of poor outcome in study present.